Stock photos of the Medford/Somerville campus in autumn, including students studying on the academic quad, fall foliage, Ballou Hall. Photo 005 - Schutzengel, Aaron (Tufts Archival Research Center, 2008)
Stock photos of the Medford/Somerville campus in autumn, including students studying on the academic quad, fall foliage, Ballou Hall.